Czynniki wpływające na stabilność pierwszych małżeństw w Polsce - Styrc, Marta (Studia Demograficzne, 2010)
Marital stability is an important topic in studies on family because of its meaning for fertility and for the well-being of children and partners. The rise of the divorce rate observed in Poland since the second half of the 1990s poses a question about factors correlated with the risk of marital disruption. In the relevant body of research, one can distinguish between factors related to partners’ characteristics, features of the relationship, and the context. The paper starts with theoretical considerations on the correlates of divorce, backed with empirical fi ndings from studies for other countries. Next, the event history regression of fi rst marriages disruption is estimated. The model is specifi ed as a piecewise constant exponential model with proportional relative risks. The data used come from the Education, Family and Employment Survey from 2006. Most of the results of this study are consistent with fi ndings for other countries: marriages with premarital children or entered into while expecting a child, as well as marriages of women brought up in bigger cities and those of employed women were less stable. The change of the educational gradient of divorce is an important fi nding – in the studies pertaining to the period before the 1990s the women with higher education showed a higher risk of divorce. In the current study, which refers to the period between the mid-1980s and 2006, marriages of women with highest education levels have the lowest risk of disruption. Surprisingly, marriages preceded by cohabitation do not have an elevated disruption risk compared to direct marriages. The impact of the presence of children on the disruption risk is lower than expected – only marriages with very small children (0-2 years old) are more stable, while parity and presence of older children do not make a difference, when compared with couples without children. In conclusion, some suggestions have been formulated regarding the data sources for the future research on the stability of unions.